The mating strategy of female Svalbard reindeer - Heatta, Maret Johansdatter (Universitetet i Tromsø, 2009)
The mating system of Svalbard reindeer was studied in detail on Nordenskiöld land, Svalbard during the mating season 2007. Little is known about the female mating systems of Svalbard reindeer. The aims of the study were to investigate the composition of harems in relation to male attractiveness, harem size and reproductive history and the associated behaviour of females. The movement patterns of marked females were studied in order to determine whether females stay in one harem throughout the rutting season. Most of the females observed were in harems, i.e. in mating groups that included males. The majority of the harems were small compared to other reindeer populations. Harems usually consisted of 1-5 females, but up to 19 females were observed in a single harem, and up to five males were associated. With increasing number of females in the harem, the number of males increased, as did the maximum male antler size. This may indicate that antler size is an indirect sign of quality for Svalbard reindeer. Females with a calf at heel were uncommon in harems, suggesting they shortly visit harems to become fertilized. The number of males associated with the harem greatly increased the proportion of time the females spent on energy consuming activities such as running and walking. The frequency of mating behaviour (male-female and female-female interactions) directed towards females increased with increasing number of females in the harem, providing evidence for greater somatic cost for females being in harems. The movement pattern of the observed females was mostly within the same valley, although some females were re-sighted in the adjacent valleys. The females were mostly re-sighted in harems, varying in size. Our results indicate that harems are dynamic entities in terms of the females attending them.